CZY JEST HOMOSEKSUALIZM W TYM TEKŚCIE? NA TROPACH NIEHETERONORMATYWNEJ TOŻSAMOŚCI BOHATERÓW KAMIENI NA SZANIEC ALEKSANDRA KAMIŃSKIEGO - Jakub Rawski (In Gremium. Studies in History, Culture and Politics, 2015)
Is it homoerotic in this text? On the trail of the identi y of characters nonheteronormative stones for the rampart by Alexander KaminskiInterpretation of the relationship Tadeusz Zawadzki ”Zośka” and Jan Bytnar ”Rudy” – heroes Stones for the rampart by Alexander Kaminski made by Elizabeth Janicka, according to which the two men combined homoerotic love, caused the Polish literary environment and media controversy. On the one hand, there are calls for „tarnish the national holiness”, on the other hand, other environmental endorsed a model of reading the text. Janicka basing their conclusions on passages from the novel Kaminski, specifically one more part, did not seriously examine philological work. This article attempts to answer the question: Is homosexuality in the text? With underlying thesis inspiring researcher, author Festung Warschau, is carried out detailed analysis of the Stones for the rampart. One of the main points of the article is an indication that the discussion is directed to novel wide audience literary text, fictional, despite existing prototypes characters actually work.